2007
DOI: 10.1051/0004-6361:20077863
|View full text |Cite
|
Sign up to set email alerts
|

The molecular and dusty composition of Betelgeuse's inner circumstellar environment

Abstract: Context. The study of the atmosphere of red supergiant stars in general and of Betelgeuse (α Orionis) in particular is of prime importance to understand dust formation and how mass is lost to the interstellar medium in evolved massive stars. Aims. A molecular shell, the MOLsphere (Tsuji 2000a, ApJ, 538, 801), in the atmosphere of Betelgeuse has been proposed to account for the near-and mid-infrared spectroscopic observations of Betelgeuse. The goal is to further test this hypothesis and to identify some of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(105 citation statements)
references
References 34 publications
10
94
1
Order By: Relevance
“…Hron et al 1998;) AGB stars, as well as for RSG stars (e.g. Perrin et al 2007). These layers were introduced earlier to explain spectroscopic observations (e.g.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hron et al 1998;) AGB stars, as well as for RSG stars (e.g. Perrin et al 2007). These layers were introduced earlier to explain spectroscopic observations (e.g.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
“…e.g. for Mira stars Ohnaka et al 2005;, and for RSG stars Perrin et al 2007;and Verhoelst et al 2009). The radiative importance of dust in an extended molecular shell depends on the local temperature, the time dependent growth rate, and the wavelengthdependent optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the first problem, a significant SiO layer just above the photosphere, which deepens the absorption band, could be present since such a layer is detected around α Ori with MIDI interferometry by Perrin et al (2007), although the SiO bandhead does not correspond well to the observed residuals around 8 μm. The current dust model may also not yet contain the correct silicate dust composition, shape, and grain size.…”
Section: Residual Dust Featuresmentioning
confidence: 99%
“…Our model assumes the same inner radius for all dust species, but the discrepancy observed here may indicate that the continuous opacity source is located even closer to the base of the wind, right above the photosphere. The detection of alumina 0.5 R above the photosphere of Betelgeuse (Verhoelst et al 2006;Perrin et al 2007) indicates that dust condensation so close to the photosphere is possible.…”
Section: Analysis Of the Residualsmentioning
confidence: 99%
“…Obviously, there is not a monotonic decrease in the mean gas temperature of the extended atmosphere from the photosphere outwards. Indeed, modeling of infrared molecular lines from RSGs has already provided evidence for the presence of cool (1500−2000 K) gas between 1.3 and 1.5 R (Tsuji 2000;Perrin et al 2004Perrin et al , 2007Ohnaka 2004;Montargès et al 2014). However, these models are not sensitive to hotter plasma that may be co-located with the cool gas.…”
Section: Verification Of a Temperature Inversion Between The Photosphmentioning
confidence: 99%